Sustainable Learning in Higher Education: Developing Competencies for the Global Marketplace - Peris-Ortiz, Marta (Springer, 2016)
In an era of globalization, technological innovation, and social transformations, universities face the challenge of training students with the competencies needed to meet the demands of the market and to successfully integrate into today’s workforce. This book looks at the university as a dynamic source of essential competencies and explores various skill management models, methodologies and innovations applied by educational institutions around the world.